COMPARISON OF FEASIBILITY ANALYSIS OF INVESTMENT WITH GRAVITY SYSTEM AND PUMPING SYSTEM IN THE IKK IBU WATER SUPPLY, WEST HALMAHERA REGENCY - Prasetyo, Baskoro Adhi; Muhammadun, Haris; Nugroho, Laksono Djoko (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
Water is a basic need for all living things on this earth, not least for individual humans themselves, that water is the support of daily activities for human survival. The average household water usage in Indonesia is 60 liters per day per person or 45% of the total usage is for drinking, cooking, washing clothes, cleaning houses and vehicles and performing worship. Kecamatan Ibu has a population of 12. 241 people who have not been covered by access to drinking water in the West Halmahera Regency area, but have a Drinking Water Supply System (SPAM) for the Sub-district Capital (IKK) which was built in 2004 supplying 700 house connections (SR) in 2 villages, namely; Maritango Village and Akeboso Village which is taken from Akeboso Spring of 20 L/Det, Since 2017 SPAM IKK Ibu has not functioned due to damage to the piping network due to road widening work, damage to generators and pumps, in this study the authors will analyze the feasibility of investment for 9 villages that will get water with a total population of 1. 102 people by estimating the Budget Plan Cost (RAB) using the PermenPU No. 1 of 2022 guidelines and calculating investment feasibility by calculating Net Present Value (NPV), Internal of Return (IRR), Benefit Cost Ratio (BCR) and Payback Period (PP) and the results obtained in the gravity system have a greater investment value of Rp 13,524,301,000 compared to the pumping system which is Rp 11,919,456,000 from the calculation of the Budget Plan Cost (RAB).